Cdk5/p25 specific inhibitory peptide TFP5 rescues the loss of dopaminergic neurons in a sub-acute MPTP induced PD mouse model. (6th October 2016) - Zhang, Qishan; Xie, Huifang; Ji, Zhong; He, Rongni; Xu, Miaojing; He, Yong; Huang, Jianou; Pan, Suyue; Hu, Yafang
Highlights: TFP5 pretreatment rescued DA neurons loss of sub-acute MPTP mice to 9.8% of control. TFP5 reduced the levels of inactive form of survival factor MEF2D and cleaved caspase 3 evoked by MPTP exposure. TFP5 prevents MPTP insulted DA neurons loss via mediated calpain-Cdk5-MEF2 signaling pathway. Abstract: Parkinson's disease (PD) is pathologically characterized by progressively loss of dopaminergic (DA) neurons in the substantia nigra pars compacta (SNpc) and the formation of Lewy bodies. In 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP) induced PD mice models, the calpain- cyclin-dependent kinase 5 (Cdk5)-myocyte enhancer factor 2 (MEF2) signaling has been proven in governing dopaminergic neuronal death. Under MPTP insult, p35 is cleaved by calpain into p25, which binds to Cdk5 and exhibits hyperactivity of Cdk5/p25. Cdk5/p25 inactivates MEF2, a survivor factor, which is critical for DA neuronal death. In this study, neuroprotective effect of the Cdk5/p25 specific peptide, TFP5, was evaluated in sub-acute MPTP induced PD mouse model by intraperitoneal (i.p.) injection of MPTP for five consecutive days. The results indicated that the levels of p35 and p25, and p25/p35 ratio increased in the sub-acute MPTP mice. TFP5 broadly reached cortex neuron, hippocampus and SNpc areas after i.p. injections. Pretreatment with 45 mg/kg/day TFP5, as well as 10 mg kg/day Cdk5 inhibitor roscovitine, for three days significantly rescued DA neuronal loss up to 9.8% or 9.7% respectively compared to the saline treated group. Treatment of TFP5 and roscovitine reduced the levels of inactive form of MEF2 and cleaved caspase 3, thus protected apoptosis of DA neurons against MPTP insult. Our results propose that TFP5 might be a potential therapeutic candidate for PD.